A member of the activator protein 1 family found in keratinocytes but not in fibroblasts required for transcription from a human papillomavirus type 18 promoter. - Offord, E A (1990)
Papillomaviruses are tissue specific and replicate in differentiating keratinocytes. We are interested in the question of tissue specificity at the level of transcription. We used extracts from human keratinocytes and human fibroblasts at low passage number and from HeLa cells to look for factors binding to the E6 promoter of human papillomavirus type 18 (HPV-18) DNA by footprint and gel mobility shift experiments. We found a factor present in HeLa and keratinocyte extracts but not in fibroblast extracts which bound about 160 base pairs upstream from the start of E6. The binding site included the sequence TGACTAAG, which resembles the consensus binding site for the AP-1 family of proteins. Synthetic oligonucleotides containing this binding site specifically competed with factor binding to HPV-18 DNA, as did the AP-1 sequence of simian virus 40. They also inhibited transcription from the E6 promoter in vitro in extracts from HeLa cells. Thus, the presence of this keratinocyte-specific factor seems to be important for HPV-18 transcription.